PEMBERDAYAAN KARANGTARUNA DENGAN KETERAMPILAN LAS KACA - LISTRIK UNTUK PENGEMBANGAN WIRAUSAHA KERAJINAN KACA - LOGAM - Purwanti Widhy Hastuti, Juli Astono, Slamet MT, (Universitas Negeri Yogyakarta, 2014)
The rasional purpose of KKN-PPM (College for Society) is reaching theenterpreneur of glass and iron handycraft as the city commodity that is done byempowermwnt Karangtaruna with the ironing skill training based on glass andelectronic iron, the targets of this program (1) improve the youth skill withtraining program in ironing skill of glass and electronic by workshop andapproachement; (2) relationing the college to improve skill making enterpreneurskill of handycraft in their city as cultural tourist resort; (3) make the stakeholderas the enterpreneur groups and meke the market share with the college;(4) make the cooperative to improve skill, capital and larger market accesibility.The method that is used is based on the prospect of entrepreneur, count of productand human skill, technology and social affect.The project methods in KKN-PPM is workshop sharing by intensivetraining until fixed the handycraft product as the commodity of cultural touristresort city in Yogyakarta regency. It can make a continuous market acces. Thetraining is done in the Mechanical Laboratory of FMIPA (Sains and MathematicsFaculty) Yogyakarta State University. The trainer is the master from RyanJaya Welding in Banguntapan Bantul and the others glass welding master.Some results of this programs (KKN-PPM) are: the Karangtaruna ofJaya Kusuma and the college have new skill of welding using electrical andglass. They can make handycraft product that can be used by the society, second,the Karangtaruna of Jaya Kusuma and the colege can make some kinds ofhandycraft, laboratory equipments like reaction tube, U tube, glass stick toteach IQRA and some welding products like book case and iron windowblocker. Eventhough this program needs several long time to mastery the skills,because the cooperative relationship must be kept continuosly and multi-yearprograms.